The urban landscape of the capital in the first half of the 1970s, the port of Vitória, public monuments and Education, confluences - Miranda, Giuliano de; Hernandez-Piloto, Sumika Soares de Freitas (Farol, 2025)
This article analyzes the transformation of the urban landscape of Vitória, Espírito Santo, between 1971 and 1975, focusing on the Port of Vitória as a structuring element. It investigates the socio-spatial impact of port expansion, including territorial reconfigurations and urban tensions. It also discusses Heritage Education as a strategy to strengthen cultural identity and collective memory, presenting the LEENA/UFES continuing education project. Using participatory action research, the study proposes integrating public monuments and Espírito Santo art into the school curriculum, aiming to develop an affective sense of belonging to the territory and interdisciplinary pedagogical practices that articulate heritage, sustainability, and inclusion in basic education schools.
Keywords: Port of Vitória; urban landscape; teacher training; heritage education; public art from Espírito Santo